Deconstructing Political Ideologies of Benazir Bhutto: A Transitivity Analysis of ‘Reconciliation: Islam, Democracy and the West’ - Waseem, Muhammad; Khan, Abdul Qadir (Annals of Human and Social Sciences, 2023)
Lexical items employed in a talk or text are not impartial. They own potential meanings and ideologies. The present study is an endeavor to deconstruct political ideologies of Benazir Bhutto in her posthumous write up Reconciliation: Islam, Democracy and the West from the perspective of SFL (Systemic Functional Linguistics). In her book, she strives to authenticate her thesis that democracy and Islam are mutually inclusive. The objective of the research is to locate the frequency indices of the processes, participants and circumstances and how among various existing political ideologies Benazir Bhutto incorporates her own political ideologies. In order to achieve the aimed targets, transitivity, a framework of SFL has been inducted to conduct the transitivity analysis of the selected text extracts. Transitivity analysis of the text discovered 128 complex clauses and 278 simplex clauses. Moreover, maximum types of processes, participants and circumstances have been used in the text. Employment of maximum transitivity elements signifies author’s encyclopedic range concerning the ideological conflict between Islam and the West. Among processes, material processes out number all other processes which indicates she is an action lady and believes in concrete action. The experiential analysis in the study also found that besides playing the role of a pacifist to reconcile democratic ideals and Islamic ideals to fill the widening lacuna between the Orients (particularly Islam) and the Occidents, Benazir Bhutto projects her own political ideologies; secularism, socialism and liberal feminism.